ответ: Na₂S + ZnCl₂ → ZnS↓ + 2NaCl
2Na⁺ + S²⁻ + Zn²⁺ + 2Cl⁻ = ZnS↓ + 2Na⁺ + 2Cl⁻
S²⁻ + Zn²⁺ = ZnS↓
MgCo3+2H(+)+2Cl(-)=Mg(2+)+2Cl(-)+CO2+H2O;
Mg(2+) + 2Cl(-)+2Na(+)+2OH(+)=Mg(OH)2+2Na(+)+2Cl(-);
Mg(OH)2+2H(+)+SO4(2-)=MgSO4+2H2O Fe2O3+3H2SO4=Fe2(SO4)3+3H2O
Fe2O3+6H(+)+3SO4(2-)=2Fe(3+)+3SO4(2-)+3H2O
Fe2O3+6H(+)=2Fe(3+)+3H2O
ответ: Na₂S + ZnCl₂ → ZnS↓ + 2NaCl
2Na⁺ + S²⁻ + Zn²⁺ + 2Cl⁻ = ZnS↓ + 2Na⁺ + 2Cl⁻
S²⁻ + Zn²⁺ = ZnS↓
MgCo3+2H(+)+2Cl(-)=Mg(2+)+2Cl(-)+CO2+H2O;
Mg(2+) + 2Cl(-)+2Na(+)+2OH(+)=Mg(OH)2+2Na(+)+2Cl(-);
Mg(OH)2+2H(+)+SO4(2-)=MgSO4+2H2O Fe2O3+3H2SO4=Fe2(SO4)3+3H2O
Fe2O3+6H(+)+3SO4(2-)=2Fe(3+)+3SO4(2-)+3H2O
Fe2O3+6H(+)=2Fe(3+)+3H2O